2018
DOI: 10.3832/ifor2749-011
|View full text |Cite
|
Sign up to set email alerts
|

Drought tolerance in cork oak is associated with low leaf stomatal and hydraulic conductances

Abstract: Biogeosciences and Forestry Biogeosciences and Forestry Drought tolerance in cork oak is associated with low leaf stomatal and hydraulic conductancesTouhami Rzigui (1-2) , Latifa Jazzar (1) , Khaoula Ben Baaziz (1) , Sondes Fkiri (1) , Zouheir Nasr (1) To investigate the role of seeds origin in drought tolerance, the response to water deprivation of cork oak seedlings differing in climatic conditions at their geographical origin was compared. Gaâfour is the provenance from the driest site and Feija is the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 39 publications
1
5
0
Order By: Relevance
“…Leaf sizes (4.6–6.8 cm 2 ) were similar to those reported by Mediavilla et al [ 28 ] for Q. suber leaves taken from different orientations in the canopy (5.5–7.4 cm 2 ) and the 7.1 cm 2 reported by Prats et al [ 20 ]. The specific leaf area values (55.6–67.8 cm 2 /g) were of the same order of magnitude as those obtained in adult leaves of Q. suber growing under contrasting environments and located in different positions and orientations of the canopy (50.0 to 126.0 cm 2 /g) [ 28 , 29 , 30 , 31 , 32 ].…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Leaf sizes (4.6–6.8 cm 2 ) were similar to those reported by Mediavilla et al [ 28 ] for Q. suber leaves taken from different orientations in the canopy (5.5–7.4 cm 2 ) and the 7.1 cm 2 reported by Prats et al [ 20 ]. The specific leaf area values (55.6–67.8 cm 2 /g) were of the same order of magnitude as those obtained in adult leaves of Q. suber growing under contrasting environments and located in different positions and orientations of the canopy (50.0 to 126.0 cm 2 /g) [ 28 , 29 , 30 , 31 , 32 ].…”
Section: Discussionsupporting
confidence: 69%
“…This finding is in line with most of the few available studies on Q. suber . Rzigui et al [ 31 ] observed that there was no difference in SLA values between two provenances in Tunisia (Gafour and Feija) with contrasting environments (125 and 126 cm 2 /g) and Daoudi et al [ 33 ] reported that SLA did not differ significantly between three humid, semi-arid and sub-humid provenances in Algeria, although SLA was lower under conditions of water deficiency. Lobo-do-Vale et al [ 32 ] reported an adaptive response to drought with an SLA reduction (85 cm 2 /g in a mild year and 65 cm 2 /g in a dry year), while Aranda et al [ 34 ] observed that, while irrigation had no significant effect, SLA decreased with increasing irradiance, thereby improving the potential for carbon uptake relative to transpiration water loss.…”
Section: Discussionmentioning
confidence: 99%
“…As for NDWI, the cork oak model only selected the climatic variable with a high correlation value (r = 0.76)short-term radiation (30 days). This result can reflect how well cork oak is adapted to the Mediterranean climate in which high irradiance values are commonly observed [41]. Although in the NDWI cork oak model the minimum temperature is selected, its influence assumes a longer period (hydrological period) and negative effect, meaning that the higher the minimum temperature in the hydrological year, the lower cell's water content of cork oak.…”
Section: Climate Influence 411 Cork Oakmentioning
confidence: 99%
“…In C 3 species, leaf hydraulic conductance is positively correlated with maximum CO 2 assimilation rates ( Brodribb et al, 2007 ), which is thought to result from higher stomatal and mesophyll conductance of CO 2 in plants with higher leaf hydraulic conductance. However, under dry conditions (high vapor pressure deficit), increased leaf hydraulic conductance results in lower WUE ( Sinclair et al, 2008 ; Rzigui et al, 2018 ). Thus, C 3 species experience a tradeoff between carbon gain and WUE.…”
Section: Contribution Of the “C 4 Syndrome” To Water Deficit Stress Tolerancementioning
confidence: 99%